Prevalence of c.2268dup and detection of two novel alterations, c.670_672del and c.1186C>T, in the TPO gene in a cohort of Malaysian–Chinese with thyroid dyshormonogenesis - Lee, Ching Chin (BMJ Open, 2015)
OBJECTIVES: The c.2268dup mutation in the thyroid peroxidase (TPO) gene is the most common TPO alteration reported in Taiwanese patients with thyroid dyshormonogenesis. The ancestors of these patients are believed to originate from the southern province of China. Our previous study showed that this mutation leads to reduced abundance of the TPO protein and loss of TPO enzyme activity in a Malaysian–Chinese family with goitrous hypothyroidism. The aim of our study was to provide further data on the incidence of the c.2268dup mutation in a cohort of Malaysian–Chinese and its possible phenotypic effects. SETTING: Cohort study. PARTICIPANTS: Twelve biologically unrelated Malaysian–Chinese patients with congenital hypothyroidism were recruited in this study. All patients showed high thyrotropin and low free thyroxine levels at the time of diagnosis with proven presence of a thyroid gland. PRIMARY OUTCOME MEASURE: Screening of the c.2268dup mutation in the TPO gene in all patients was carried out using a PCR–direct DNA sequencing method. SECONDARY OUTCOME MEASURE: Further screening for mutations in other exonic regions of the TPO gene was carried out if the patient was a carrier of the c.2268dup mutation. RESULTS: The c.2268dup mutation was detected in 4 of the 12 patients. Apart from the c.2268dup and a previously documented mutation (c.2647C>T), two novel TPO alterations, c.670_672del and c.1186C>T, were also detected in our patients. In silico analyses predicted that the novel alterations affect the structure/function of the TPO protein. CONCLUSIONS: The c.2268dup mutation was detected in approximately one-third of the Malaysian–Chinese patients with thyroid dyshormonogenesis. The detection of the novel c.670_672del and c.1186C>T alterations expand the mutation spectrum of TPO associated with thyroid dyshormonogenesis.